1994
DOI: 10.1128/mcb.14.1.416-426.1994
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of two functionally and structurally distinct domains of the c-fos AU-rich element specifies its mRNA-destabilizing function

Abstract: AU-rich elements (ARE) in the 3' untranslated region of many highly labile mRNAs for proto-oncogenes, lymphokines, and cytokines can act as an RNA-destabilizing element. The absence of a clear understanding of the key sequence and structural features of the ARE that are required for its destabilizing function has precluded the further elucidation of its mode of action and the basis of its specificity. Combining extensive mutagenesis of the c-fos ARE with in vivo analysis of mRNA stability, we were able to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(7 citation statements)
references
References 29 publications
1
4
0
2
Order By: Relevance
“…A further analysis of the c-fos ARE was published while our manuscript was in the final stages of preparation (17) and has shown, consistent with our findings, that the AUUUA-containing region is sufficient to promote deadenylation and degradation of a heterologous mRNA, while the downstream U-tract alone is not. In contrast to our findings, however, this U tract was found to have an enhancing effect on deadenylation when placed either 5' or 3' of the AUUUA motifs.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A further analysis of the c-fos ARE was published while our manuscript was in the final stages of preparation (17) and has shown, consistent with our findings, that the AUUUA-containing region is sufficient to promote deadenylation and degradation of a heterologous mRNA, while the downstream U-tract alone is not. In contrast to our findings, however, this U tract was found to have an enhancing effect on deadenylation when placed either 5' or 3' of the AUUUA motifs.…”
Section: Resultssupporting
confidence: 88%
“…1) containing the promoter and 5'UTR from c-fos, a translated region encoding human growth hormone, and a 3'UTR and downstream polyadenylation signals from bovine growth hormone. The fos promoter responds transiently to a shift from low to high serum in the culture medium, resulting in a pulse of transcription lasting less than 1 h, and has been used by others in studies of mRNA degradation (3,17,47,48). This inducible promoter was used in preference to a constitutive promoter to allow mRNA degradation rates to be mea- 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have shown that in the ARE‐mediated mRNA decay deadenylation precedes decay of the body of the mRNA (Chen and Shyu, 1994; Chen et al ., 1994, 1995). To address further which step in the c‐ fos ARE‐mediated decay pathway is affected by HuR, we have performed additional time‐course experiments with time points up to 480 min.…”
Section: Resultsmentioning
confidence: 99%
“…β 2 -AR mRNA appears to be similar to other highly regulated mRNAs [e.g., mRNAs of granulocyte/macrophage colonystimulating factor (GM-CSF), tumor necrosis factor-R (TNF-R), and the oncogenes c-myc and c-fos] that are markedly influenced by alterations of their rates of degradation (15)(16)(17)(18)(19). In addition to the ARE of β 2 -AR mRNA, cognate sequences of 3′-untranslated regions (UTR) of mRNA, such as the tandem repeats of AUUUA pentamers (10)(11)(12)(13)(20)(21)(22) and nonamers, such as UUAUUUA(U/A) (U/A) (23) and UUAUUUAUU (24), are important elements in determining RNA stability.…”
mentioning
confidence: 99%